Does sex predict quality of life after acute coronary syndromes: an Australian, state-wide, multicentre prospective cohort study. Issue 12 (18th December 2019) - Koh, Youlin; Stehli, Julia; Martin, Catherine; Brennan, Angela; Dinh, Diem T; Lefkovits, Jeffrey; Zaman, Sarah
Abstract : Objective: Women have reported higher mortality and major adverse cardiovascular events (MACE) following acute coronary syndromes (ACSs) compared with men. With this in mind, we aimed to identify predictors of poor quality of life (QoL) post-ACS as our primary outcome. We examined predictors of MACE, major cerebrovascular events and major bleeding as our secondary outcome. Design: Prospective cohort study. Setting: 30 metropolitan centres across the Victorian Cardiac Outcomes Registry network. Participants: 16 517 patients treated with percutaneous coronary intervention (PCI) for ACS (22.9% females). Selection/inclusion criteria: consecutive patients with successful or attempted PCI for ACS from 2013 to 2016, alive at 30 days post-PCI. Exclusion criteria: patients not fulfilling ACS criteria. At 30 days, 2497 (64.7% females) completed the QoL EQ-5D-3L instrument. Primary and secondary outcome measures: QoL, assessed using the EuroQo-5Dimensions (EQ-5D-3L) instrument by telephone at 30 days. Independent predictors of QoL were identified by univariate and multivariate logistic regression analyses. Results: Women were significantly older with more diabetes, cerebrovascular disease and renal failure. Regarding the primary outcome, female sex was independently associated with moderate/severe impairment in all EQ-5D-3L domains including mobility (OR 2.38, 95% CI 2.06 to 2.75, p<0.001), personal care (OR 2.14, 95% CI 1.73 to 2.66, p<0.001), activities of daily living (OR 1.84, 95% CI 1.63 to 2.08, p<0.001), pain/discomfort (OR 1.44, 95% CI 1.24 to 1.67, p<0.001) and anxiety/depression (OR 1.49, 95% CI 1.30 to 1.70, p<0.001). Women had significantly lower self-rated Visual Analogue Scale scores (80.0 for both groups, IQR 60-85 vs 70-90, p<0.001). There was no significant difference between the sexes in secondary outcomes. Conclusions: Female sex was a predictor of poorer QoL following PCI for ACS including significantly higher pain, anxiety and depression. This was independent of age, comorbidities and ACS presentation. There is a clinical need for a tailored approach in female ACS management, for example, emphasis on management of depressive and anxiety symptoms.